SOCIAL WELFARE AND THE TEACHINGS OF THE QUR'AN: ANALYZING THE INTERRELATIONSHIP BETWEEN SOCIAL CONCEPTS AND QUR'ANIC VALUES - Dhiya Azelia B. Lubis; Fuqarra Haqqi (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2022)
Abstract This study explores the intersection between social welfare concepts and Qur'anic values, focusing on principles such as justice, equality, and solidarity. It analyzes key Qur'anic verses and how these teachings contribute to the development of a holistic and sustainable model of social welfare. By employing a qualitative approach, including content analysis of the Qur'an and case studies from Muslim-majority countries such as Malaysia and Saudi Arabia, the research investigates the practical application of Islamic principles in contemporary welfare policies. The findings suggest that Islamic teachings, particularly the practices of zakat and sadaqah, provide an ethical framework that enhances the sustainability, equity, and inclusivity of social welfare systems. By comparing these with secular welfare models, the study highlights the potential for integrating spiritual values into modern welfare strategies, offering a more comprehensive and balanced approach to addressing social and economic inequalities. This research contributes to the understanding of how Qur'anic values can be applied to promote justice and social cohesion in contemporary welfare policies.